The Contemporary Social Work Practices in India and Australia: Literature Review - Dev, Priya S; Sangeeta, Sangeeta (Nusantara Journal of Behavioral and Social Science, 2025)
Social Work is a profession that emerged out of humanitarian philosophy and participatory ideologies. The values of social work profession are based on dignity and worth of the individuals and groups in the society. For social inclusion and development, it attempts to alleviate poverty and to enhance the vulnerable and suppressed people in different segments of the society. Hence, the profession works for preventing the dysfunction among individuals, groups and communities through developing them with full potential. Social work supported humanitarian grounds might even be an age old idea in India and the West. We will see it from a historical perspective throughout the ages. It is envisaged in the United States of America as a service to mankind and compassion for the poor and underprivileged. Since the past, the system of the society has modified — the straightforward and uncomplicated societies have currently become complicated and complex ones. This dynamic sphere of the society has given rise to several personal and social issues, which, in turn, have created Social work activities as associated organized Social work profession. Globally Social work is one, among the fastest-growing professions and is extraordinarily in demand. Regardless of dealing with individuals alone or in groups, the Social Workers are doing a variety of jobs in the human services process.This paper deals with the evolution of social work, that inside the western and eastern countries, particularly relating to India and Australia.